The art of the (im)possible in Heart Failure - Capel, Rebecca; Cox, Sally; Puntoni, Sarah (International Journal of Population Data Science, 2025)
Objectives Understanding compliance with the national heart failure (HF) clinical pathway can help drive improvement in early diagnosis. In Wales, this is limited by the lack of nationally reported echocardiograms (ECHOs). Through collaboration between clinicians and analysts, various proxy measures were tested to assess performance against the intended interventions. Methods The NICE guideline for HF diagnosis from primary care referrals requires a simple B-type natriuretic peptide (BNP) blood test to assess the need and urgency for an ECHO as the gold standard diagnostic test. Clinicians and analysts collaborated to test compliance with the national standard using existing nationally held datasets. Due to the lack of nationally reported ECHOs and the Outpatients Appointments Dataset (OPA) only available at specialty level, innovative approaches were employed. Using the Welsh Results Reporting dataset (WRRS), patients with raised BNP identified in primary care were linked to the OPA, to trace them in a Cardiac specialty. Results Patients were traced to determine if they had received a cardiology appointment within 6 weeks of a raised BNP (>= 400ng/L) over the past 5 years. Recognising that not all raised results necessitate a referral, we explored three denominator approaches: all patients with raised results, those referred following a raised result, and those with an appointment post-referral. Each approach yielded different outcomes: Included all patients with raised BNP, providing a broad overview but potentially overestimating compliance. Focused on those referred, offering a more targeted measure but excluding patients not referred despite raised results. Patients with appointments post-referral, provided the most specific measure but was limited by incomplete data. These variations highlight the challenge in accurately measuring compliance to guidelines using existing data. Conclusion Improving data quality and standardisation through PACS (Picture Archiving and Communication System) investment, collaboration across NHS organisations, and acquisition of National Institute for Cardiovascular Outcomes Research (NICOR) data is crucial. Standardising coding, data submission, and reporting, along with mandating regular audits, will enhance national data consistency and accuracy.